Beyond The Arabic-English Dichotomy: Language As A Catalyst For Islamic Civilizational Renewal In The Global Era - Khairul Azmi; Sutarmo Sutarmo (Ikatan Cendikiawan Ilmu Pendidikan Islam (ICIPI), 2026)
The relationship between global languages and Islamic thought is considered to have two opposite roles. Where Arabic is prioritized because it is the purest and most valid language to study Islamic science. While English is considered a tool to spread western influence or dominance. This perspective causes differences in various educational contexts in Muslim regions, including Indonesia. So that it makes scientific ideas and innovations from within the country difficult to be recognized and disseminated to the world level. This research examines how Islamic principles such as Shumuliyyah (universality) and Maqashid al-Shariah change the perspective so that foreign languages are not considered a religious threat, but rather as a means by which academics function to transmit knowledge. This study uses a qualitative literature research design on 26 reference sources, including the Qur'an, literature studies, classical books, which are analyzed through qualitative thematic analysis, The results of the research synthesis show that Arabic remains the most legitimate main language for understanding revelation (Religion). However, English is very important as a tool for disseminating knowledge, building academic networks, and engaging in intercultural dialogue. Based on the purpose of Islamic law (Maqashid Sharia), mastering international languages actually helps to maintain reason (hifz al-'aql) and spread religion (hifz al-din) at the world level. In theory, this study provides a religious perspective to get out of the extreme choice of self-isolation or too westernization in language rules. Practically, this research helps Islamic campuses see mastery of foreign languages as an important skill, not just being forced to assimilate into Western culture.